Improvement of Noise and Gain Characteristics of Low-Repetition-Rate Double-Pass Fiber Amplifiers - Rao Li; Wei Fan; Xiaochao Wang; Xuechun Li (IEEE Photonics Journal, 2019)
The noise and gain characteristics of pulsed double-pass (DP) amplifiers operating at low repetition rates are analyzed theoretically and experimentally. The Frantz–Nodvik equations are extended to realize rapid calculation of signal gain in DP fiber amplifiers. At the same time, the rate equations are used to compute the evolution of amplified spontaneous emission (ASE) noise. The effects of the pump scheme, the input energy, and the insertion loss on the gain and noise characteristics are discussed. Based on the simulation results, a new structure Yb-doped DP amplifier is proposed. The experimental results show that the small-signal gain of the DP amplifier can exceed 50 dB. In particular, the average ASE background of the DP amplifier at high-energy output is lower than that of the single-pass amplifier at the same output. This result is quite different from continuous-wave fiber amplifiers.